2005
DOI: 10.1292/jvms.67.281
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Feature of Barks of Ovariohysterectomized and Intact German Shepherd Bitches

Abstract: ABSTRACT. This study was carried out to investigate the effect of ovariohysterectomy on vocalization during territorial aggression of German Shepherd dogs. Sixteen clinically healthy dogs of 5 to 10 months old were assigned randomly to one of two groups: ovariohysterectomy or control. Their behaviors and vocalizations induced by the approach of a stranger with a strange dog were recorded using digital camcorder at four and five months after surgery and were analysed. When territorial aggression was induced, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…On the other end of the shyness-boldness spectrum, several studies have reported an increase in fearfulness and/or reactivity associated with gonadectomy. This included increased fearfulness in gonadectomized female Labrador Retrievers [212] and gonadectomized Vizslas of both sexes [112], as well as reactivity and vocalization in ovariectomized German Shepherd females [224,225].…”
Section: Boldness-related and Aggressive Behaviormentioning
confidence: 99%
“…On the other end of the shyness-boldness spectrum, several studies have reported an increase in fearfulness and/or reactivity associated with gonadectomy. This included increased fearfulness in gonadectomized female Labrador Retrievers [212] and gonadectomized Vizslas of both sexes [112], as well as reactivity and vocalization in ovariectomized German Shepherd females [224,225].…”
Section: Boldness-related and Aggressive Behaviormentioning
confidence: 99%
“…In one study, ovariohysterectomised female German shepherd dogs were more reactive to the presence of unfamiliar humans and dogs and barked more than intact females (Kim et al., 2005). In a later study of the same group, reactivity scores were assigned to intact and ovariohysterectomised German shepherd dogs, when an unfamiliar human leading an unknown dog approached.…”
Section: Health Detriments Of Sterilisation With Loss Of Reproductive...mentioning
confidence: 99%
“…Neutering has been suggested to impact behaviour in female dogs by many authors (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, considerable variation between study populations and methodology, alongside contradictory findings, make associations unclear for many behaviours.…”
Section: Introductionmentioning
confidence: 99%